2022
DOI: 10.1038/s44160-022-00145-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistically informed selection rules for competing β-hydride and β-heteroatom eliminations

Abstract: Alkylpalladium complexes are important intermediates in several industrially relevant catalytic reactions such as the Mizoroki-Heck, alkyl C-H activation and ethylene polymerisation. β-elimination -of either a hydride (β-Η) or a heteroatom (β-Χ) -is the most common decomposition pathway for these intermediates; this can either lead to the desired reaction as in the Mizoroki-Heck reaction, or it can hinder reaction progress as in ethylene/vinyl halide co-polymerisations. Despite the importance of these eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 88 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Though there could be competition between β-H and β-Cl elimination in FeS-mediated dechlorination of CEs, the low pK a H (the aqueous pK a of the conjugate acid) of the chlorines was recently identified to favor the β-Cl elimination. 72 Therefore, β-Cl elimination was preferentially enabled in the abiotic dechlorination of TCE and DCEs. DCEs with two chlorines were converted to acetylene through dichlorine elimination.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there could be competition between β-H and β-Cl elimination in FeS-mediated dechlorination of CEs, the low pK a H (the aqueous pK a of the conjugate acid) of the chlorines was recently identified to favor the β-Cl elimination. 72 Therefore, β-Cl elimination was preferentially enabled in the abiotic dechlorination of TCE and DCEs. DCEs with two chlorines were converted to acetylene through dichlorine elimination.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Interestingly, this study found that OHRB could promote FeS-mediated PCE-to-acetylene dechlorination by providing less-chlorinated ethenes (e.g., TCE and DCEs). Though there could be competition between β-H and β-Cl elimination in FeS-mediated dechlorination of CEs, the low p K a H (the aqueous p K a of the conjugate acid) of the chlorines was recently identified to favor the β-Cl elimination . Therefore, β-Cl elimination was preferentially enabled in the abiotic dechlorination of TCE and DCEs.…”
Section: Discussionmentioning
confidence: 99%
“…45 Additionally, an experiment (see pg S99) was run with an OMs leaving group which has been demonstrated by Morandi and co-workers to prefer β-hydride elimination over β-OMs elimination in an inner sphere mechanism but still generates a mixture of those two products. 45 Under our conditions only styrene�the product of β-OMs elimination�is observed. This further supports an outer sphere elimination mechanism from the anion.…”
mentioning
confidence: 99%
“…We chose to explore the mechanism using derivatives of 3a due to the 19 F NMR spectroscopy tag and the availability of the starting materials. Three potential intermediates of the organic fragment that could form product are that of (1) a radical intermediate, 44 (2) an anionic intermediate formed from radical-polar crossover, and (3) an inner sphere β-halide elimination from an organometallic species generated from two-electron oxidative addition of 3 to 2 45,46 (Figure 4). The results of no competition between elimination of bromide versus fluoride in Figure 3e suggest the leaving group ability governs this selectivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation